José Echegaray, a multi-faceted mathematician: Nobel Prize in Literature, an outstanding politician, promoter of Spanish physics and mathematics at the end of the 20th century and the beginning of the 20th: José Echegaray, un matemático polifacético: Premio nobel literatura, político destacadísimo, impulsor de la física y mate española al final del siglo IXX y de principios del XX. - Arguedas T., Vernor (2019)
Some aspects of the rich life of Don José Echegaray are discussed, both mathematical, political, literary as well as cultural in the turbulent Spain of the second half of the 19th century and the beginning of the 20th century.